Graft Survival and Segment Discards Among Split‐Liver and Reduced‐Size Transplantations in the United States From 2008 to 2018. Issue 2 (13th December 2021) - Montgomery, John R.; Highet, Alexandra; Brown, Craig S.; Waits, Seth A.; Englesbe, Michael J.; Sonnenday, Christopher J.
Abstract : Split‐liver transplantation has allocation advantages over reduced‐size transplantation because of its ability to benefit 2 recipients. However, prioritization of split‐liver transplantation relies on the following 3 major assumptions that have never been tested in the United States: similar long‐term transplant recipient outcomes, lower incidence of segment discard among split‐liver procurements, and discard of segments among reduced‐size procurements that would be otherwise "transplantable." We used United Network for Organ Sharing Standard Transplant Analysis and Research data to identify all split‐liver (n = 1831) and reduced‐size (n = 578) transplantation episodes in the United States between 2008 and 2018. Multivariable Cox proportional hazards modeling was used to compare 7‐year all‐cause graft loss between cohorts. Secondary analyses included etiology of 30‐day all‐cause graft loss events as well as the incidence and anatomy of discarded segments. We found no difference in 7‐year all‐cause graft loss (adjusted hazard ratio [aHR], 1.1; 95% confidence interval [CI], 0.8‐1.5) or 30‐day all‐cause graft loss (aHR, 1.1; 95% CI, 0.7‐1.8) between split‐liver and reduced‐size cohorts. Vascular thrombosis was the most common etiology of 30‐day all‐cause graft loss for both cohorts (56.4% versus 61.8% of 30‐day graft losses; P = 0.85). Finally, reduced‐size transplantation was associated with a significantly higher incidence of segment discard (50.0% versus 8.7%) that were overwhelmingly right‐sided liver segments (93.6% versus 30.3%). Our results support the prioritization of split‐liver over reduced‐size transplantation whenever technically feasible.